2017
DOI: 10.1007/s00423-017-1628-z
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of lymph node metastases and their size in colon cancer

Abstract: It is necessary to resect 10 cm of normal bowel both proximal and distal to the tumor and to perform D3 lymph node dissection for ≥ T2 colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…For the LN+ group, according to pathological results, cases with a metastatic LN ratio of ≥0.8 were included, which meant metastatic LNs/harvested LNs ≥0.8. The area located ≤5 cm from the distal edge of the tumor, which had a higher incidence of metastatic LNs (20). According to the surgical records, the area of the corresponding LNs was determined.…”
Section: Methodsmentioning
confidence: 99%
“…For the LN+ group, according to pathological results, cases with a metastatic LN ratio of ≥0.8 were included, which meant metastatic LNs/harvested LNs ≥0.8. The area located ≤5 cm from the distal edge of the tumor, which had a higher incidence of metastatic LNs (20). According to the surgical records, the area of the corresponding LNs was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of resection of the colon is decided with the aim of removal of possible metastatic paracolic lymph nodes. Investigation of the pattern of lymph node metastases along the colon has shown that the probability of lymph node metastases further than 10 cm from the tumour is less than 1 per cent, so the 10‐cm rule is most frequently used to determine the point of transection of the bowel.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Fujii et al ., 100% of patients with distant regional lymph node (N2) metastasis had a G3/G4 cancer type [ 7 ]. In the studies of Rössler et al ., the primary tumour of patients with lymph node metastases was classified as G2 in 3.28%, G3 in 47.54%, and G4 in 49.18% [ 9 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%